2019
DOI: 10.1073/pnas.1906643116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic LAMP2 deficiency accelerates the age-associated formation of basal laminar deposits in the retina

Abstract: The early stages of age-related macular degeneration (AMD) are characterized by the accumulation of basal laminar deposits (BLamDs). The mechanism for BLamDs accumulating between the retinal pigment epithelium (RPE) and its basal lamina remains elusive. Here we examined the role in AMD of lysosome-associated membrane protein-2 (LAMP2), a glycoprotein that plays a critical role in lysosomal biogenesis and maturation of autophagosomes/phagosomes. LAMP2 was preferentially expressed by RPE cells, and its expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 74 publications
(104 reference statements)
4
44
0
Order By: Relevance
“…Further, we found increased lipid droplets and esterified cholesterol, which is associated with drusen in humans and sub-RPE deposits in mouse models. A recent study using RPE-specific LAMP2 knockout mouse showed faulty processing of ingested OS, lipid accumulation, and similar RPE deposit protein composition 28 as compared to this current study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Further, we found increased lipid droplets and esterified cholesterol, which is associated with drusen in humans and sub-RPE deposits in mouse models. A recent study using RPE-specific LAMP2 knockout mouse showed faulty processing of ingested OS, lipid accumulation, and similar RPE deposit protein composition 28 as compared to this current study.…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, a recent study showcased that the levels of LAMP2/CD107b (a lysosomal membrane protein) are reduced in AMD RPE/choroid tissues 28 . Observation of similar sub-RPE deposits in TEM micrographs in Cib2 mutant mice prompted us to investigate the molecular composition of the deposits.…”
Section: Molecular Characterization Of Sub-rpe Deposits In Cib2-deficmentioning
confidence: 99%
See 1 more Smart Citation
“…Though mechanisms remain to be elucidated, the LAMP family of lysosome-resident glycoproteins is indeed required for the fusion of lysosomes with the phagosome (103). It is therefore noteworthy, that the loss of just one of these family members, LAMP2, in the murine RPE causes delayed POS degradation and the build-up of POS debris (104). In fact, the loss-of-function mutations in LAMP2 that cause Danon disease in humans is also associated with retinal and macular degeneration (105).…”
Section: Phagosome Maturationmentioning
confidence: 99%
“…Autophagy is an essential process for all cells, but its function is especially notable in post-mitotic cells such as those in the RPE 16 that have the highest life-long phagocytic load of any cell-type in the body. Defects in autophagy has been implicated in dry AMD 17,18 . Besides AMD, deficits in autophagy are linked to lifespan and several diseases such as Alzheimer's, Parkinson's, certain cancers, and metabolic disorders amongst others [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%